IMPLEMENTASI PENDIDIKAN KARAKTER PADA SISWA DI SMA NEGERI 3 DENPASAR - I Made Arsa Wiguna (Guna Widya: Jurnal Pendidikan Hindu, 2017)
This paper aims to describe the implementation of character education to students in SMA Negeri 3 Denpasar. Its don’t need to doubt about the existence of this high school because of the achievements. Its can not be separated from character education that is manifestly implemented in the in the classroom or outside the classroom learning. Principals and teachers believe that the purpose of education should be returned to the original goal of forming a good character.